Epitaxial Stitching and Stacking Growth of Atomically Thin Transition‐Metal Dichalcogenides (TMDCs) Heterojunctions. (9th January 2017) - Chen, Kun; Wan, Xi; Xu, Jianbin
Abstract : In recent years, ultrathin two‐dimensional (2D) transition metal dichalcogenides (TMDCs), such as MX2 (M = Mo, W; X = S, Se, etc.) have become the flagship materials after graphene. 2D‐MX2 have attracted significant attention due to their novel properties arising from their strict dimensional confinement as well as strong spin–orbit coupling effects, which provides an ideal platform for exploring new fundamental research and realizing technological innovation. The 2D nature and the small lattice mismatch between MX2 make them ideal templates for construction of vertical and lateral heterojunctions at atomic scale by means of CVD epitaxial growth. This feature article aims to introduce current advances in the preparation of vertical or lateral epitaxial heterostructures based on 2D MX2 nanosheets as well as their potential applications in electronics, and optoelectronics. Firstly, various epitaxial CVD strategies for synthesis of vertical or lateral 2D MX2 heterostructures are comprehensively reviewed. Meanwhile, the advantages of these epitaxial methods as well as several applications of 2D MX2 heterostructures, such as photodiodes and photovoltaic devices are highlighted. Then the remaining challenges facing the controllable syntheses and the future perspectives of this promising area are discussed. Abstract : Two‐dimensional transition‐metal dichalcogenide (2D TMDCs) heterojunctions offer new and exciting opportunities to fabricate novel devices with unprecedented performance. Currently, the chemical vapor deposition technique (CVD) has displayed great promise to prepare lateral or vertical epitaxial TMDCs heterostructures. An overview of recent progress in the epitaxial growth of heterojunctions on the basis of ultrathin TMDCs and their potential application is presented.